Serum IL-6, IL-10, TNF-α changes after of manual lymphatic drainage combined with abdominal breathing in the rehabilitation of postpartum perineal edema : Serum IL-6, IL-10, TNF-α after Postpartum - Xue, Lili (Journal of Medical Biochemistry, 2025)
Objective: This study aims to evaluate the effectiveness of manual lymphatic drainage (MLD) combined with abdominal breathing in the rehabilitation of postpartum perineal edema and Serum IL-6, IL-10, TNF-α. Methods: A total of 172 primiparous women who delivered in our hospital between January 2022 and June 2023 were randomly assigned to either the observation group (n=86) or the control group (n=86). The control group received routine midwifery care, while the observation group received additional MLD and abdominal breathing training. Outcomes measured included pain levels, induration diameter, comfort, emotional state, recovery time, and clinical efficacy. Inflammatory markers, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α), were also assessed. Results: Both groups demonstrated significant reductions in Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores after treatment (P<0.05), with the observation group showing a greater decrease (P<0.05). The observation group exhibited a significantly shorter recovery time (3.6±1.8 days vs. 4.2±2.5 days, P<0.05) and reported higher comfort levels and lower pain scores than the control group (P<0.05). The effective treatment rate was 97.68% in the observation group, significantly higher than the 82.56% observed in the control group (P<0.05). Inflammatory markers, including IL-6 and TNF-α, showed a significant reduction in the observation group compared to the control group (P<0.01), suggesting a positive impact on inflammatory resolution and tissue healing. Conclusion: The combination of abdominal breathing and MLD effectively accelerates the regression of perineal edema, alleviates pain, improves psychological well-being, and enhances postpartum comfort. Additionally, it contributes to reducing inflammation and promoting faster recovery, making it a valuable approach for postpartum rehabilitation following vaginal delivery.